PELATIHAN PENERAPAN MODEL RHOMI (REALISTIC AND HOLISTIC MATHEMATICS INTEGRATION) BAGI GURU DALAM MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA DI SMPN 8 KOTA SUNGAI PENUH - Rhomiy Handican; Ahmad Yani; Riki Saputra; Ade Putra Hayat; Agung Tri Prasetia; Syukron Saputra (Institut Agama Islam Negeri Kerinci, 2025)
This community service program aimed to enhance teachers’ competencies in implementing mathematics instruction oriented toward the development of students’ critical thinking skills through training on the RHOMI (Realistic and Holistic Mathematics Integration) model. The program was conducted at SMPN 8 Kota Sungai Penuh using a Participatory Action Research (PAR) approach, positioning teachers as active participants throughout all stages of the program, including planning, action, observation, and reflection. The PAR approach was selected to ensure that the training was participatory, contextual, and sustainable, in line with teachers’ actual classroom needs. The results indicated an improvement in teachers’ understanding of realistic and holistic mathematics learning, as well as a shift in instructional practices from procedural teaching toward more dialogical, reflective, and critical-thinking-oriented learning. Teachers were able to design RHOMI-based instructional materials that integrated real-life contexts with mathematical concepts in a coherent manner. Furthermore, the program fostered collaboration and reflective practices among teachers. Therefore, the PAR-based RHOMI training proved to be an effective community service strategy for improving the quality of mathematics instruction and enhancing students’ critical thinking skills